دراسة تجريبية للتربة المحليّة المغلفة لكابلات الطاقة الكهربائية الأرضية - محمد زهيرة; وائل حرفوش; يحيى إبراهيم علي (Tishreen University, 2019)
يتعلق الاستثمار الأمثل لكابلات الطاقة الكهربائية المدفونة بالأرض، بالخواص الفيزيائية والحرارية للتربة المغلفة لها. ويهدف هذا البحث لإجراء دراسة تجريبية لمعرفة الخواص الفيزيائية والحرارية لثلاث عينات من التربة المحلية المستخدمة لهذا الغرض، وتحديد أفضل العينات المختبرة. وقد أجريت التجارب الفيزيائية للعينات الثلاثة في مخبر ميكانيك التربة بجامعة تشرين، أما الخواص الحرارية فقد تمت دراستها بواسطة جهاز اختبار تم تصنيعه محليا وفق معايير ونظم الهيئة الدولية الكهروتكنيكية IEC. وقد بينت النتائج التجريبية، أن عينات التربة المختبرة هي ذات خواص جيدة عند استخدامها في تغليف كابل واحد، أما عند زيادة عدد الكابلات المدفونة مع بعضها فكانت هذه الخواص سيئة، وذلك بسبب هجرة الرطوبة ونشوء المنطقة الجافة حول الكابلات، حيث تزداد فيها المقاومة الحرارية النوعية للتربة المغلفة، مما يؤدي لفشل الكابلات وانهيارها. ولحل هذه المشكلة، والتقليل من تأثير المنطقة الجافة حول الكابلات، فقد تم تحديد أنسب العينات المختبرة وهي رمل الكسارات Soil(3)، ومزجها مع الغبار الصخري الناعم بنسبة معينة. حيث بينت نتائج التجربة، تحسين الخواص الفيزيائية والحرارية لهذه العينة بشكل كبير، مما يجعلها ذات مواصفات جيدة لاستخدامها كتربة مغلفة لعدة كابلات مدفونة مع بعضها. The optimum employment for underground electric power cables is related to the thermal and physical properties of the backfill soil. This study aims to perform experimental research work to investigate the thermal and physical properties for three samples of local soil used for this purpose, and to determine the best tested samples. The physical tests on the three samples were performed at the soil mechanic laboratory in Tishreen University; however, the thermal properties were studied through employment of a testing device that is locally made, viewing the standards applied by IEC. The experimental results proved that the tested local soil samples possess good properties when used to backfill one cable, but when increasing the number of the underground installed cables, these properties were bad, due to moisture migration and formation of dry zone around the cables where we view an increase in the specific thermal resistance to the backfill soil, which leads to failure and breakdown of cables. To solve this problem, and decrease the effect of the dry zone surrounding the cables, determination was made for the best experimented sample which is soil (3), then to mix some with the soft rock dust in specific ratios. Showed an the results improvement in the thermal and physical properties for this sample to a large extent, which will render it having good characteristics to be used as backfill soil for several burried together cables.